Protagonismo da leitura : escola e formação de leitores (Alvorada/RS) - Bitencourt, Tamara Véras de (2014)
The aim of this study was to contextualize the place of reading in Basic Education, more specifically, in the final grades of Elementary School. It starts of problematic about the existing paradox between recurrent speech that students do not read and / or cannot read and how the reading appears in daily school, It was used the Ideb 's of two municipal schools of Alvorada / RS for the choice of contexts to be researched . The methodological resources used were: literature review, questionnaires to identify the reader profile of subjects and ethnography of the classroom. The schools were chosen according to Ideb 's 2011 : Municipal Elementary School Herbert Jose de Souza the most Ideb, and Municipal Elementary School Antonio Godoy the lowest Ideb. In each of the schools a class of seventh grade and their teachers formed the corpus of subjects of this research. In addition to students and teachers, the responsible for school supervision and responsible for libraries also answered questionnaires. The researcher followed the two selected classes for a period of thirty days, composing the ethnography. The protagonism of reading is seen only in its informative dimension. Students read to learn the contents, without that they are taught to read. The readers profiles, both students and teachers, are very similar and do not justify the difference in Ideb 's of two schools. The library of school with the most Ideb was more engaged with the formation of readers than the school with the lowest index. The ethnographic writing becomes apparent the little space dedicated to reading and problems that students and teachers have faced in routine of the school. This study appoints to the need to think about the training of teachers as responsible for the development of literacy throughout the final grades of Elementary School. For the reading becomes protagonist in the school context, it has to be understood in all its dimensions and functions, mainly, it must be the responsibility of all.